Connectivity between countries established by landbirds and raptors migrating along the African–Eurasian flyway - Guilherme, João L. (2022)
The conservation of long-distance migratory birds requires coordination between the mul-tiple countries connected by the movements of these species. The recent expansion oftracking studies is shedding new light on these movements, but much of this informationis fragmented and inaccessible to conservation practitioners and policy makers. We synthe-sized current knowledge on the connectivity established between countries by landbirdsand raptors migrating along the African–Eurasian flyway. We reviewed tracking studies tocompile migration records for 1229 individual birds, from which we derived 544 migra-tory links, each link corresponding to a species’ connection between a breeding country inEurope and a nonbreeding country in sub-Saharan Africa. We used these migratory linksto analyze trends in knowledge over time and spatial patterns of connectivity per country(across species), per species (across countries), and at the flyway scale (across all countriesand all species). The number of tracking studies available increased steadily since 2010 (par-ticularly for landbirds), but the coverage of existing tracking data was highly incomplete.An average of 7.5% of migratory landbird species and 14.6% of raptor species were trackedper country. More data existed from central and western European countries, and it wasbiased toward larger bodied species. We provide species- and country-level syntheses of themigratory links we identified from the reviewed studies, involving 123 populations of 43species, migrating between 28 European and 43 African countries. Several countries (e.g.,Spain, Poland, Ethiopia, Democratic Republic of Congo) are strategic priorities for futuretracking studies to complement existing data, particularly on landbirds. Despite the limi-tations in existing tracking data, our data and results can inform discussions under 2 keypolicy instruments at the flyway scale: the African–Eurasian Migratory Landbirds Action Plan and the Memorandum of Understanding on the Conservation of Migratory Birds ofPrey in Africa and Eurasia.